ANALISIS PERBANDINGAN BIAYA KULIAH PROGRAM STUDI S1 AKUNTANSI ANTAR PERGURUAN TINGGI SWASTA DI BEKASI - Anisa Putri (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Islam 45, 2021)
The purpose of this study was to identify the tuition fee components and to analyze the comparison of tuition fees for the undergraduate accounting study program at private universities in Bekasi. The research method uses descriptive methods. The type of data is secondary data. The data analysis used is descriptive qualitative method. The results showed that the component of tuition fees for undergraduate accounting study programs at private universities in Bekasi consisted of registration fees, development costs, tuition fees per semester, laboratory fees, practice fees, exam fees (UTS and UAS), proposal fees and thesis fees, and graduation fee. The total cost of studying an undergraduate accounting study program at private universities in Bekasi is the most expensive, namely Esa Unggul University. The total cost of studying an undergraduate accounting study program at a private university in Bekasi is the most expensive, namely STIE BII. The total value of tuition fees varies for each private university in Bekasi.